Analysis of Budget and Realization Financial Performance at the Labuhanbatu Utara Regency Personnel and Human Resources Development Agency - Harahap, Siti Tasya Zulaikha; Syafina, Laylan; Nasution, Yenni Samri Juliati (Universitas Muhammadiyah Sorong, 2024)
This research aims to determine the performance and financial realization of the budget in five budget years, namely 2018-2022 at the North Labuhanbatu Regency Personnel and Human Resources Development Agency. This research uses a qualitative approach, with documentation procedures used to obtain data. The analytical approach used is a descriptive method which includes spending variance analysis, spending growth analysis, spending alignment analysis (divided into operational spending and capital spending), and efficiency ratios. Research findings using expenditure variance analysis for 2018-2022 show that the performance of the expenditure budget is quite good because no expenditure exceeded the budget. Based on a review of state spending growth from 2018 to 2022, there is a positive increase with an average of 8,41%. Based on the findings of the 2018-2022 expenditure alignment study, the expenditure budget is used more for operational expenditure than capital expenditure. With an average operational expenditure over the five budget years of 98,10%, capital expenditure was 1,90%. Based on the 2018-2022 budget realization efficiency ratio, the efficiency level of budget use in 2018 was 79,76%, while the efficiency level in 2019-2022 budget use was quite efficient with budget use of 84,80%, amounting to 81,74%, 83,02%, and 85,20%.